The Business Case for Cyber-Threat Information Sharing - Ward, Jesse (Rural Telecommunications, 2019)
How can you best apply your limited resources to protect and defend your networks against the most probable and damaging threats? A critical input into your organization's risk management plan is access to timely and actionable threat intelligence-intel that is gained through active, voluntary participation in robust information sharing forums. Once the foundation was in place, pilot participants exchanged cybersecurity information via a variety of online platforms; participated in weekly virtual meetings to shara cyber intelligence, hear from subject matter experts and collaborate w th their peers; and received curated content from NTCA, including a daily cyberthreat report summarizing open-source news items and alerts fron DHS, and a weekly technical report on exploits and vulnerabilities. In an era of interconnected networks with increased focus by policymakers and regulators on cybersecurity, active, voluntary engagement in cyber information sharing forums demonstrates the rural telecom industry's commitment to the security of your customers, business enterprises and the larger global community. ?